1 IMPLIKASI PERATURAN PEMERINTAH NOMOR 109 TAHUN 2012 TERHADAP INDUSTRI ROKOK KECIL DI KUDUS - Sukma Gunadi; Ahmad Taufiq; Neny Marlina (Journal of Politic and Government Studies, 2017)
ABSTRACTKudus cigarette industry experienced a long journey, over 120 years old. From day to day the number of the Kudus tobacco industry in decline, especially small cigarette industry. In 2010 the number of small cigarette industry in the Kudus reach 209 business units and in 2013 jumalahnya stay 33 business units. Coupled with the enactment of Government Regulation No. 109 of 2012 on Safety Materials Containing addictive substances such as tobacco products for Health will make a small cigarette industry in Kudus more screaming. This study aims to determine the impact ditimbukan from the Government Regulation No. 109 of 2012. It also wants to know how the efforts of the tobacco industry are small and Kudus District Government in overcoming the impact of the enactment of Government Regulation No. 109 of 2012 so that it can survive to date.This research method using descriptive qualitative research. Source of data in will come from direct interviews with a small cigarette industry players in the Kudus and the Department of Labor, Industry, Cooperatives and SMEs district. Kudus and secondary data. The selected sampling is purposive sampling system, the sampling technique with a certain consideration. Data collection techniques that can be used in this study were interviews, and literature.The impact of the imposition of PP 109 Year 2012 will make a small cigarette industry or group 3 increasingly difficult to continue its efforts. Since the content in PP 109 Year 2012 mostly regulates the marketing of the tobacco industry as well as in the aspect of packaging, additives, and the content of which will have an impact on production costs rise. Kudus District Government's role in addressing these impacts and maintain the existence of a small cigarette industry is by way of guidance and vocational training programs and the establishment of LIK-IHT.Realizing the enormity of the role of the tobacco industry for the economy of the Kudus society, the government must protect the small cigarette industry in Kudus by issuing regulations that favor small cigarette industry .. The government needs to participate in regulating the tobacco trade regulation mechanisms to protect them from the game of speculators price of course the producers of small cigarette.Keywords: Safety Materials, addictive substances, Tobacco Products, Healthcare, Small Cigarette Industry